HUMAN CAPITAL FORMATION USING BUSINESS SIMULATION MODELS - Skunčikienė, Solveiga; Rakickas, Andrius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The subject of the analysis in this paper is human capital formation at the individual level, applying business simulation models as a learning tool that meets requirements of the modern learning process that should include and link personal experience, encourage thinking, acquisition of new knowledge, formation of new experience and its application in analysing practical situations.The subject of the research paper: human capital formation using business simulation model.The aim of the research - to analyze the application possibilities of business simulation models for the human capital formation.To achieve the aim of the research the following tasks were set: to disclose the concept of business simulation model; to validate the applicability of business simulation models for human capital formation on the basis of empirical research.The subject of the analysis in this paper is human capital formation at the individual level, applying business simulation models as a learning tool that meets requirements of the modern learning process that should include and link personal experience, encourage thinking, acquisition of new knowledge, formation of new experience and its application in analysing practical situations.Research methods: analysis of scientific literature using operations of analysis and synthesis, comparison and systematization, questionnaire survey, and the following methods of statistical data analysis.